The wild little horse - Gray, Rita.; Wolff, Ashley (New York : Dutton Children's Books, 2005)
Little Horse cannot resist the call of the wind, which encourages him to run like a wild colt and cavort by the sea.
Accelerated Reader AR
Keywords: Horses -- Fiction; Play -- Fiction; Winds -- Fiction; Seashore -- Fiction; Stories in rhyme